Antioxidant Potential Of Ethylacetate Fraction Of Cynodon Dactylon Against Ela Implanted Swiss Albino Mice - M.SAROJA,; R.SANTHI,; S.ANNAPOORANI, (International Journal of Pharma and Bio Sciences, 2012)
The study was carried out to determine the level of enzymic and non enzymic antioxidants in Ehrlich’s Lymphoma Ascite (ELA) transplanted mice treated with ethylacetate fractions of Cynodon dactylon. The levels of enzymic antioxidants like super oxide dismutase, glutathione peroxidase and catalase and non enzymic antioxidants like reduced glutathione, vitamin A and vitamin E were decreased in ELA induced mice due to the liberation of free radicals from the liver. Administration of ethylacetate extracts showed increased levels of enzymic and non enzymic antioxidants in ELA transplanted mice. The result suggests that ethylacetate fractions possessed lipid peroxidation inhibiting activity. Thus it could be concluded that ethylacetate fractions possess antioxidant activity.